Evaluation and design of an adapted endobutton fixation system to be used in conjunction with suture and endobutton techniques for the treatment of coronoid process fractures - Mason, Nicola (Department of Human Biology, 2026)
Introduction: The coronoid process is a critical anatomical structure of the elbow, playing a fundamental role in the joint's stability. Fractures of the coronoid, typically resulting from high-energy impact, can disrupt this stability and compromise the elbow joint posing a significant challenge to the Orthopaedic surgeon. 3D imaging and fracture mapping are becoming the standard practice for visualising the fractured area and a means of planning surgical treatment. Although there is an ongoing debate about the ideal method of treating coronoid fractures, there are several recommended surgical fixation options. One of the available fixation devices is the Endobutton. This dissertation's primary aim is to design an adapted Endobutton using fracture mapping and Q3DCT techniques. The secondary aim is to evaluate the existing Endobutton to establish criteria for comparison and assessment of the newly designed device. Methods and Materials: Sixty-three upper limb computer tomography (CT) scans depicting coronoid fractures were acquired from Groote Schuur Hospital. Q3DCT techniques were used to generate fracture maps from multiple views. This involved editing CT scans to render 3D models of fractures and subsequent in-silico reduction and mapping. These were complimented by the generation of heat maps depicting the fracture line density. Templating and a qualitative assessment, performed by three Orthopaedic surgeons, evaluated the currently used Endobutton, leading to the establishment of evaluation criteria. This was followed by an iterative conceptual and detailed design process that was used to develop the adapted Endobutton. The designed device was verified through rapid prototyping, templating, and comparative qualitative assessment. Subsequent validation of the design was done using simulated surgeries in cadaver limbs, followed by the same comparative qualitative assessment. Results & Discussion: The 3D fracture and heat maps enable comprehensive inspection of the coronoid fractures from multiple views, thus facilitating the identification of the recurring patterns on the anterior surface of the bone. Fracture type specific critical fracture patterns and weak points of the bone's structure are identified. These insights inform the design of an adapted Endobutton. The templating and assessment of the commercially available Endobutton underscore its inefficacy in addressing coronoid fractures, highlighting the limitations that the designed adapted Endobutton aims to mitigate. Verification results indicate that the adapted Endobutton design yields improved qualitative user data, which suggests its enhanced performance as a fixation method compared to the commercially available Endobutton. The validation results reinforce the improved qualitative outcomes for Type 2 and Type 3 coronoid fractures, however the outcomes for Type 1 favour the commercially available device. Overall observations note that a spiked and curved asymmetrical design offer a more congruent fit to the bone, as well as effectively fitting over the majority of the fracture fragments. Conclusion: The commercially available Endobutton leads to unfavourable reduction and fixation qualitative parameters when compared to the newly designed adapted Endobutton. The new design demonstrates promising potential as an effective approach to coronoid fracture fixation as evidence by its effective application to the 3D-printed fractures and cadaver specimens.